(untitled) (Research, Society and Development, 2021)
Objective: To describe the factors associated with self-perceived health in diabetics according to the results of a nationwide population survey. Methods: We used data from the National Survey on Access, Use and Promotion of the Rational Use of Medicines (PNAUM), a nationwide population survey conducted from September 2013 to February 2014. Results: A worse self-perception of health was observed among diabetics who: had 3 or more CD representing 14.9% (95%CI: 12.6-17.5), than those who had only 1 CD 3.7% (95%CI: 1.7-7.8) ; They had other chronic diseases such as CVA 21.3% (95%CI: 14.1-30.9), Chronic joint disease 17.8% (95%CI: 13.4-23.3) and Depression 24.0%(CI95 %:18.1-31.1); They had any limitation due to diabetes and who sought the emergency service 30.5% (95%CI: 21.4-41.5) and underwent hospital admissions 20.80% (95%CI: 14.2-29.3 ) in the last 12 months due to Diabetes Conclusion: Those users who had 3 Chronic Diseases or more, other chronic diseases, had any limitation due to diabetes and had health service care due to the disease, rated their self-perception of health worse. The use of users’ self-perceived health assessment during consultations with professionals can be used as a tool in structuring the targeted therapeutic plan. As it is an indicator of health outcomes, self-perception of health can be assessed in conjunction with the personal and individual context of each patient, so that we can provide more comprehensive and targeted health care for each patient.